Ecological effects of ENSO phenomenon in Colombia - Carvajal, Yesid (1999)
The ENSO phenomenon has a substantial effect on global climate variation; therefore, it is not surprising that its effects have a strong ecological and socio-economic impact, altering the feeding security world around. In front of this, it is understandable the awake world interest, not only by meteorology and oceanography specialists, but also among biologists, hydrologists, economists, sociologists and planners, among others. The present work shows some principal ecological effects in Colombia during the warm phase (El Niño) and cold phase (La Niña) pointed out the necessity to orientate the investigation in causes, consequences and impacts.